Effect of certain additives on the freezability of crossbred bull semen - SRIVASTAVA, SUSHANT; KUMAR, S (The Indian Journal of Animal Reproduction, 2023)
Thirty two ejaculates (8 each from FH and FxH bulls) were subjected to freezing. Cervical mucus penetration test and hypo-osmotic swelling test used for quality assessment of fresh and frozen thawed spermatozoa. Sperm penetration distance (SPD) travelled by vanguard spermatozoa of HF and FxH bulls were 45.06 ± 3.32 and 39.94 ± 2.98mm of fresh semen and 19.69 ± 0.47 and 18.38 ± 0.59mm of fresh semen in 60 min. SPD traveled by vanguard spermatozoa differed significantly (P<0.01) among the bulls and between the breed. HOS positive sperm for HF and FxH semen was 49.38 ± 2.80 and 42.06 ± 3.57 of fresh semen and 21.88 ± 0.44/hr and 21.00 ± 0.57/hr of frozen thawed sperm. A significant difference (P<0.01) in total swollen sperm was observed between );,reeds and between the two crossbred bulls significantly (P<0.0 I) between HF bulls in frozen semen. A significant positive correlation of HOS positive sperm and SPD with mass motility, initial progressive motility, live count, percent intact acrosome, post-thawed motility, post thaw livability and post thaw intact acrosomc and negative correlation (P<0.01) with total sperm abnormalities were recorded. A significant (P<0.0 I) improvement was recorded after incorporation of ascorbic, caffeine and chloroquine in diluter. Maximum improvement was recorded in presence of ascorbic acid. Since SPD and HOS tests rneasure the functional and structural normality and subsequent fertility of spermatozoa. these tests can be used as predictor for fertility of frozen semen and ascorbic acid can be supplemented in the freezing media for obtaining better post-thaw recovery.